NEGOTIATING BORDERS: IMMIGRATION, DISPLACEMENT, AND CULTURAL CONFLICT IN DIVAKARUNI’S WORKS - Nixson. B.; E. Anita (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Chitra Banerjee Divakaruni, a renowned Indian-American writer, presents a compelling portrayal of the immigrant experience in her literary works, particularly emphasising the intertwined processes of immigration and emigration. This article explores the nuanced representation of diasporic life in Divakaruni’s fiction, focusing on key themes such as intergenerational conflict, cultural displacement, and identity negotiation. Her characters often inhabit the liminal space between cultures, struggling to balance assimilation with cultural preservation and the deep human need for belonging. This study situates Divakaruni’s work within the broader landscape of immigrant literature through a critical analysis of her narratives and the incorporation of secondary sources. It highlights how her storytelling contributes meaningfully to contemporary dialogues surrounding diaspora, cultural hybridity, and the complexities of transnational identity.